Penguatan Literasi Anti-Bullying Remaja Melalui Edukasi Komprehensif Berbasis Media Visual Interaktif - Waliamin, Janusi; Jerri Pratama; Muhammad Ilham; , Muhamad Riski; , Palendo Ricardo; Rahmat Taufiq (Bengkulu Institute, 2025)
During the Kuliah Kerja Lapangan (KKL) held from February 16 to 21, 2025, 90 Management students from the Faculty of Economics and Business, University of Hazairin (FEB Unihaz), participated in activities at several partner industry locations in the Special Region of Yogyakarta (DIY) and Central Java Provinces. One of the locations visited was the Batik Village of Giriloyo. Activities carried out during the field work included the signing of cooperation agreements, outreach sessions, and batik-making practice. During the batik-making practice, students had the opportunity to be creative and innovative in designing batik patterns. This activity helped enhance students’ creative thinking skills.